Assessing the effects of climate change and other factors on rice yield of farmers in Tagum City, Davao del Norte - Prudencio, Leon Gabriel B. (2018)
Climate change is currently affecting the production of major crops, such as rice. Fortunately, there are adaptation practices that can mitigate the effects of climate change on rice production. Other factors that can affect production of rice are socio-demographic characteristics, farm production inputs, and climate change perception of rice farmers. The general objective of this study was to assess the effects of climate change and other factors on the rice yield of farmers in Tagum City, Davao del Norte, Philippines. Specifically, the study aimed to determine the effects of temperature and rainfall patterns, socio-demographic factors, farm production inputs, and climate change perception of rice farmers and to recommend adaptation practices that can better increase their rice productivity. A total of 172 farmers were interviewed from five different barangays in Tagum City. Data were analyzed using descriptive statistics. Tobit Regression Model was used to determine the effects of climate change and other factors on rice yield in three separate years (2012, 2015, 2017). Using t-test analysis, results showed that the average annual yield of farmers were significantly different in 2012, 2015 and 2017. Average annual temperature and rainfall patterns in the area were also significantly different from 2008-20017. Inputs to production were not significantly different across the three years. Results from the Tobit Model indicate common factors with statistically significant effects on yield such as farmers? income, education, farm size, labor, using hybrid varieties and no tillage processes. The study concluded that climate change is present in the area but with no conclusive evidence on its exact effects to rice yield. It is recommended for farmers to invest in education, pursue off-farm activities, focus more on adopting hybrid varieties of rice, increase chemical use, employ no tillage processes, change cropping schedules, and have irrigation systems. LGUs in the study area should take role in implementing such avenues that can increase farmers? rice yield.